2015
DOI: 10.1088/0004-6256/150/6/201
|View full text |Cite
|
Sign up to set email alerts
|

Color Systematics of Comets and Related Bodies

Abstract: Most comets are volatile-rich bodies that have recently entered the inner solar system following long-term storage in the Kuiper belt and the Oort cloud reservoirs. These reservoirs feed several distinct, short-lived "small body" populations. Here, we present new measurements of the optical colors of cometary and cometrelated bodies including long-period (Oort cloud) comets, Damocloids (probable inactive nuclei of long-period comets) and Centaurs (recent escapees from the Kuiper belt and precursors to the Jupi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
177
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(206 citation statements)
references
References 78 publications
27
177
2
Order By: Relevance
“…The extreme case of 167P/CINEOS, which has the largest perihelion distance (q = 11.8 au) among the active Centaurs, has been used as a case study for numerical simulations of the survival of amorphous water ice against crystallisation, which is considered the most probable trigger of comet-like activity at such heliocentric distances (Guilbert-Lepoutre 2012). Jewitt (2015) has recently shown, based on a sample of 37 targets (12 of which with evidence of activity), that active Centaurs tend to be those with smaller perihelion distances, as is expected for comet-like activity driven by a thermal process.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…The extreme case of 167P/CINEOS, which has the largest perihelion distance (q = 11.8 au) among the active Centaurs, has been used as a case study for numerical simulations of the survival of amorphous water ice against crystallisation, which is considered the most probable trigger of comet-like activity at such heliocentric distances (Guilbert-Lepoutre 2012). Jewitt (2015) has recently shown, based on a sample of 37 targets (12 of which with evidence of activity), that active Centaurs tend to be those with smaller perihelion distances, as is expected for comet-like activity driven by a thermal process.…”
Section: Introductionmentioning
confidence: 78%
“…4, where the diameter D of 42 Centaurs is shown as function of the perihelion distance q, and in Fig. 5, where the diameter of 40 Centaurs is given as a function of the semi-major axis a (Jewitt 2009(Jewitt , 2015Stansberry et al 2008;Shi & Ma 2015;Pál et al 2015;Mazzotta Epifani 2011, 2014aLin et al 2014;Duffard et al 2014). For clarity, two values of a outside the Centaur region (between Jupiter's and Neptune's orbits) have been removed from the sample (31 inactive targets and 11 active targets) in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 5. B -V vs.V -R color-color plot adapted from Jewitt (2015) to show the location of U1 relative to other solar system small-body groups. The red circles denote sub-populations of the Kuiper Belt; the blue circles show the mean colors of inner solar system populations.…”
Section: Comet or Asteroid?mentioning
confidence: 99%
“…They found that the reflectivity gradient decreases with wavelength from 5-18 per cent per 100 nm at wavelengths 0.35-0.65 μm to 0-2 per cent per 0.1 nm at 1.6-2.2 μm. An interesting and extensive overview has been done by Jewitt (2015). He find that the mean optical colours of the dust in short-period and long-period comets are identical within the uncertainties of measurement, as are the colours of the dust and of the underlying nuclei.…”
Section: O L O U R a N D R E F L E C T I V I T Y O F T H E D U S Tmentioning
confidence: 99%